(untitled) (Olhar de Professor, 2022)
This text discusses the application of large-scale evaluations to special education students. If firstly addresses the theme of large-scale evaluations and how they have become benchmarks for the quality of education in international and national contexts. Prova Brasil is approached in a more specific way. The way in which the inclusion of these students has been carried out through the National Policy for Special Education in the Inclusive Education Perspective (Política Nacional de Educação Especial na Perspectiva da Educação Inclusiva – PNEEPEI) is also investigated. Finally, the article discusses how the inclusion process of special education students has been in the daily routine of schools and how it occurs or not regarding the application of Prova Brasil. The data analyzed were collected using semi-structured interviews with teachers, educators, and principals of three public schools located in the northern plateau of Santa Catarina, Brazil. Thematic analysis was chosen as the data analysis method. Our conclusions pointed out that the inclusive perspective presented in the PNEEPEI goes against aspects related to large-scale evaluations, specifically Prova Brasil. Furthermore, we highlighted that the logic of the exam is perverse with both teachers and students, especially those ones of special education.